The role of women in production and management of RTB crops in Rwanda and Burundi: Do men decide and women work? - Okonya, Joshua Sikhu (International Potato Center, 2018)
Presented by Joshua Okonya (CIP/RTB), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.